B7–H3 as a Prognostic Biomarker and Therapeutic Target in Pediatric central nervous system Tumors - Maachani, Uday B. (Transl Oncol, 2019)
B7–H3 (CD276), a member of the B7 superfamily, is an important factor in downregulating immune responses against tumors. It is also aberrantly expressed in many human malignancies. Beyond immune regulatory roles, its overexpression has been linked to invasive metastatic potential and poor prognosis in patients with cancer. Antibody-dependent cell-mediated cytotoxicity strategies targeting B7–H3 are currently in development, and early-phase clinical trials have shown encouraging preliminary results. To understand the role of B7–H3 in pediatric central nervous system (CNS) malignancies, a comprehensive panel of primary CNS tumors of childhood was examined by immunohistochemistry for levels and extent of B7–H3 expression. In addition, B7–H3 m-RNA expression status and association with overall survival in various pediatric CNS tumor types was accessed by curating publicly available patient gene expression data sets derived from bioinformatics analysis and visualization platforms (GlioVis). We demonstrate that B7–H3 is broadly expressed in pediatric glial and nonglial CNS tumors, and its aberrant expression, as determined by immunohistochemical staining intensity, correlates with tumor grade. Moreover, high B7–H3 m-RNA expression is significantly associated with worse survival and could potentially improve prognostication in various brain tumor types of childhood. B7–H3 can be used as a therapeutic target, given its tumor selectivity and the availability of targeted therapeutic agents to this antigen.